The legal and diplomatic role of the Baltic States in Russia's war against Ukraine - Tīrmanis, Kristens (Riga Graduate School of Law, 2023)
The main research in this thesis will focus on the diplomatic and legal assistance provided by the Baltic States to Ukraine after it was attacked by the Russian army. Accordingly, the thesis will study how the assistance provided by the Baltic States has contributed to, and may in the future influence, the outcome of this conflict. It is clear that in this case the Baltic States are limited in their support due to their financial resources, territorial size, and overall influence, but the main objective is to find out whether countries like the Baltic States are able to influence an ongoing conflict involving a country like Russia, which is much more influential territorially and economically. The research reveals that the Baltic States are capable of influencing the course of the conflict and by engaging in various forms of legal assistance Russia can later possibly be held accountable for its crimes.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Russia; Ukraine; Baltic States; Legal and diplomatic support